Perpektif Makna Cinta dalam Kumpulan Puisi Esai Atas Nama Cinta Karya Denny JA [The Perspective of Meaning of Love in the Compilation of Poetry Titled "Atas Nama Cinta" by Denny JA] - Pitaya Rahmadi (Diligentia: Journal of Theology and Christian Education, 2021)
The community plays a role in empowering the use of literary works, including, in this case, poetry essays to express the realities that happened in society. Through the five essay poems written by Denny JA, various facts are presented to be used as lessons for readers as part of society. This collection of stories of different kinds of love offered by Denny JA opens the eyes and awakens the readers' minds that love is no love is never free or natural. Love is still imprisoned by religion, discrimination, by the moral norms of society. Is there true love that transcends religion, overcomes discrimination, and is above the moral norms of society? This collection of five poetry essays Atas Nama Cinta by Denny JA serves as a starting point for reflections to answer the restlessness expressed inf the series of questions above. The meaning of love as described by Denny JA raises the perspective of both internal social problems related to the psyche due to conflicting thoughts that exist in the person's character—and externally associated with the character's interaction with the surrounding environment. The meaning of love needs to be reconstructed to convey educational values to readers as part of society. Literary works, including poetry, are not only psychological expressions of the author but also reflect recorded records of various events in a community so that poetry can present a history of conflicts that exist in the author's memory.